CORRELATION OF SUPPORTING INFORMATION COMPLETENESS FACTORS WITH THE ACCURACY OF DISEASE CODING AT 'AISYIYAH SITI FATIMAH HOSPITAL OF SIDOARJO - Mellania, Nova; Rossarini, Anna; Nisak, Umi Khoirun; Cholifah, Cholifah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Based on the data obtained from the observation on the inpatient medical record file of the Hospital 'Aisyiyah Siti Fatimah Tulangan Sidoarjo that the initial data shows that there are still medical record files with inaccurate diagnosis codes that do not match as much as (33%). The purpose of this study is to determine the relationship between the completeness of supporting information factors that affect the accuracy of disease coding in inpatient medical record files at the 'Aisyiyah Siti Fatimah Hospital, Tulangan Sidoarjo. This research method uses quantitative research with correlational research which has the aim of determining whether or not there is a relationship between two or more measurable variables. Data collection was carried out in August-October using a check list sheet by observing the inpatient medical record data. The population in this study were all inpatient medical record files in August-October 2021 and the sample in this study was 231 inpatient medical record files at the Hospital 'Aisyiyah Siti Fatimah Tulangan Sidoarjo with random sampling which was presented in the frequency table and cross tabulation, then tested using the Chi Square Test.The results of the Chi Square test of this study indicate that the supporting information completeness factor variable has a relationship with the accuracy of disease coding because the p value <0.05, which means Ho is rejected. The results show that the p value of the completeness of supporting information factor = 0.022.In this study, it is recommended to improve the quality of coding by increasing the completeness of the file, and can produce an accurate data by conducting coding training and evaluating coding audits to support the accuracy of disease coding.